2016
DOI: 10.1071/wr15209
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of feral horses (Equus caballus) in an exotic coniferous plantation in Australia

Abstract: Context Understanding population dynamics of invasive species is crucial for the development of management strategies. Feral horses (Equus caballus) are a growing problem in the Tuan–Toolara State Forest (TTSF), a coniferous plantation in south-eastern Queensland, Australia. Aim The population dynamics of the TTSF feral horses was not known. Therefore, the study was designed to characterise the major vital parameters of this population and, using these data, develop a long-term management plan. Methods The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…As a consequence, the demographic parameters of the population increased and resulted in a moderate finite growth rate (λ = 1.10), almost doubling the population growth rate observed during 1995-2002 (λ = 1.06). This value is similar (λ = 1.06-1.10) to what has been reported in food-limited feral horse populations (Linklater et al 2004, Dawson and Hone 2012, Richards et al 2014, Zabek et al 2016) but lower than observed in other populations (λ = 1.15-1.30; Eberhardt et al 1982, Garrott and Taylor 1990, Grange et al 2009 Elasticity analysis of demographic parameters estimates their relative contribution to the population growth rate and potential targets for management (Caswell 2000, De Kroon et al 2000. The value of elasticity of adult female survival in the study population was higher than elasticity of survival of foal, yearling, and juvenile females, and also higher than adult female fecundity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As a consequence, the demographic parameters of the population increased and resulted in a moderate finite growth rate (λ = 1.10), almost doubling the population growth rate observed during 1995-2002 (λ = 1.06). This value is similar (λ = 1.06-1.10) to what has been reported in food-limited feral horse populations (Linklater et al 2004, Dawson and Hone 2012, Richards et al 2014, Zabek et al 2016) but lower than observed in other populations (λ = 1.15-1.30; Eberhardt et al 1982, Garrott and Taylor 1990, Grange et al 2009 Elasticity analysis of demographic parameters estimates their relative contribution to the population growth rate and potential targets for management (Caswell 2000, De Kroon et al 2000. The value of elasticity of adult female survival in the study population was higher than elasticity of survival of foal, yearling, and juvenile females, and also higher than adult female fecundity.…”
Section: Discussionsupporting
confidence: 85%
“…Long‐term studies (i.e., ≥5 yrs) of individually identified feral horses are scarce (Berger 1986, Garrott and Taylor 1990, Goodloe et al 2000, Grange et al 2009, Richard et al 2014). Matrix population models from feral horse demographic data and elasticity analyses have been conducted on data from New Zealand (Linklater et al 2004), Australia (Zabek et al 2016), and Canada (Richard et al 2014), but none of these studies validated their population size projections with independent data from another study period.…”
mentioning
confidence: 99%
“…Understanding population dynamics and the processes that influence them is critical for management of populations. In Australia, there are few demographic studies on wild horses [5,10,16], particularly within woodland habitats [17,18]. In south-east Australia, although free-roaming horses commonly reside in woodland habitats (eucalyptus forests) and undulating and often steep terrain, population and demographic data for horses in these habitats are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of developing scientific methods for capturing data to enable the assessment of the welfare of free-roaming wild animals has recently been highlighted [1]. Many studies have evaluated wild horse behaviours, time budgets, home ranges, body condition scores and social organisation, e.g., [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], but to date, an extensive range of welfare indicators has apparently not been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation